METHODOLOGY OF COMPANY’S EFFICIENCY ASSESMENT - Primzharova K.; Beimbetova А.; Abdrashev J. (Academic Journal of Physical and Chemical Sciences, 2020)
At the current stage of Kazakhstan development, the competitiveness of companies and the relevance of their future activities are based primarily on the efficiency of their work. Efficiency is the basic factor of company’s financial attractiveness for external investors, as well as for the owners of the business. Thus, it is very important to assess the effectiveness of the company in all stages of lifecycle, in the present, past and future. The article focuses on the methodology for assessing the efficiency of the company, as well as provides methodological recommendations for assessing the economic efficiency of the company in modern business conditions. Studying the questions of the essence, the main forms of performance indicators of the enterprise as an economic category. Looking for the methodology of generalization of modern approaches to the problem, finding the features of assessing the economic efficiency of the enterprise, developing proposals to improve the economic efficiency of the company. One of the main challenges of the economy is the increasing efficiency of production and business activity. The economic efficiency of the company depends on the best way of using all types of resources and their structure, which is involved in various production factors. In the system of social efficiency, the economic efficiency is determined by total production efficiency on both micro and macro-levels. On the macro-level, total production efficiency is expressed by economic efficiency of different sectors and national economy in general. On the micro-level by the efficiency of business entities and their divisions. In order to get sufficient results of economic efficiency assessment it is important to have systematic assessment. Systematic assessment of economic efficiency is expressed by few factors. To evaluate it as a socio-economic category, we have to take into account the social side. Not always economically justified production can be socially effective. This contradiction may occur in case of poor regulatory framework of employees’ rights protection. At the same time, it should be noted that social and industrial aspects are mutual interrelated and affecting each other.